The complete guide to personal digital archiving - Marshall, Brianna H. (Facet Publishing, 2018)
"Scholars and scrapbookers alike need your help with saving their most important digital content. But how do you translate your professional knowledge as a librarian or archivist into practical skills that novices can apply to their own projects? The Complete Guide to Personal Archiving will show you the way, helping you break down archival concepts and best practices into teachable solutions for your patrons' projects"--provided by publisher.